Motion Detection from Mobile Robots with Fuzzy Threshold Selection in Consecutive 2D Laser Scans. - Martínez-Sánchez, María Alcázar; Martínez-Rodríguez, Jorge Luis; Morales-Rodríguez, Jesús (My University, 2015)
Motion detection and tracking is a relevant problem for mobile robots during navigation to avoid collisions in dynamic environments or in applications where service robots interact with humans. This paper presents a simple method to distinguish mobile obstacles from the environment that is based on applying fuzzy threshold selection to consecutive two-dimensional (2D) laser scans previously matched with robot odometry. The proposed method has been tested with the Auriga-α mobile robot in indoors to estimate the motion of nearby pedestrians.
Keywords: Movimiento - Detección; Robótica; Algoritmos difusos; Motion sensing; Pedestrian detection; Data segmentation; Fuzzy algorithm; Mobile robot; Laser rangefinder